Simple preparation and microwave absorption of TERGO/ZnO porous composites. (December 2022) - Liu, Xin; Zhang, Fengcao; Lu, Xiaolong; Sun, Minglei; Liu, Xiubo; Yu, Zexin; Liu, Zhongqing; Zhao, Dong; Wang, Mingdi
Abstract: TERGO/ZnO porous composites with light weight, high porosity and good absorption properties were obtained by the method of heat treatment and hydrolysis process, which are simple to prepare and have a more uniform porous structure. After the facile thermal expansion, GO deoxidizes and rapidly expands to form a thermally expansion reduced graphene oxide (TERGO) porous structure with uniform and small pore size distribution. Subsequently, ZnO particles are uniformly dispersed in the surface or layer spacing of TERGO by hydrolysis to improve its impedance matching and interfacial polarization. Furthermore, expanded graphite (EG)/ZnO composites are prepared for comparison. The TERGO/ZnO composite shows excellent microwave absorption with a reflection loss bandwidth (≤ −10 dB) covering the X-band at 3.9 mm thickness. This research will provide guidelines for the preparation of microwave absorbers with low cost, porous, and good performance.